2009
DOI: 10.1021/ja905959n
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C Dynamic Nuclear Polarization in Aqueous Solution with a Two-Field (0.35 T/14 T) Shuttle DNP Spectrometer

Abstract: Dynamic nuclear polarization (DNP) permits increasing the NMR signal of nuclei by pumping the electronic spin transitions of paramagnetic centers nearby. This method is emerging as a powerful tool to increase the inherent sensitivity of NMR in structural biology aiming at detection of macromolecules. In aqueous solution, additional technical issues associated with the penetration of microwaves in water and heating effects aggravate the performance of the experiment. To examine the feasibility of low-field (9.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 18 publications
1
46
0
3
Order By: Relevance
“…Due to the contribution of scalar hyperfine interaction this value is considerably lower than the maximum value of 0.5 that is expected for pure dipolar interaction in the limit of low polarization fields/high temperatures. This is in qualitative agreement with literature data [29][30][31], which shows that 13 C Overhauser DNP enhancements are very sensitive to scalar coupling contributions. From power-dependent measurements of the 13 C DNP signal (not shown) a relative saturation factor of 75% can be calculated for a microwave power of 5.7 W. The maximum saturation factor as well as the leakage factor at this radical concentration is expected to be close to unity [20].…”
Section: Resultssupporting
confidence: 93%
“…Due to the contribution of scalar hyperfine interaction this value is considerably lower than the maximum value of 0.5 that is expected for pure dipolar interaction in the limit of low polarization fields/high temperatures. This is in qualitative agreement with literature data [29][30][31], which shows that 13 C Overhauser DNP enhancements are very sensitive to scalar coupling contributions. From power-dependent measurements of the 13 C DNP signal (not shown) a relative saturation factor of 75% can be calculated for a microwave power of 5.7 W. The maximum saturation factor as well as the leakage factor at this radical concentration is expected to be close to unity [20].…”
Section: Resultssupporting
confidence: 93%
“…We developed a pneumatic system for fast shuttling, based on a system that was originally developed for liquid-state dynamic nuclear polarization (DNP) studies where the proton polarization observed at 14.1 T can be enhanced by saturating EPR transitions at 0.34 T. 35 Our shuttle consists of a custom-designed probe (Figure 2a,b), a transfer system, and a control unit, as described in more detail in Supporting Information. The probe uses two saddle coils, like in standard high-resolution probes.…”
Section: Resultsmentioning
confidence: 99%
“…Another approach that is consequently being explored consists of polarizing the sample at lower magnetic fields, where the sample size is less restricted, and transferring the sample afterwards to the high NMR detection field. [194,198] Such “shuttle DNP” implementations have included performing Overhauser DNP at low (0.35 T) fields, where radicals such as TEMPOL can be easily saturated and will efficiently transfer their magnetization to nearby protons, followed by sample shuttling to high fields (600 MHz) for final NMR detection. The shuttling is based on a pneumatic operation (Figure 15) that minimizes the distance between the high- and low-field position and ensuring a monotonous increase in the B 0 field between the two positions.…”
Section: Increasing Sensitivity By Spin-alignment Transfer Strategmentioning
confidence: 99%